An examination of advanced cancer caregivers' support provided by staff interventions at hospices in Argentina - Luxardo, Natalia (2012)
The aim of the study was to describe the type of intervention provided by hospice staff in order to address the pragmatic, psycho-social, and spiritual needs of home-caregivers for patients in the last stage of cancer. The qualitative inquiry was carried out in real life contexts. The explicit demands that caregivers (n = 40) identified in the first interviews were: (1) helping to organize the care of the patient at home; (2) unspecific demands, with unclear or unrealistic purposes (e.g., curative treatment or a miracle expected to occur); (3) specific resources (such as formal caregivers to replace them), and (4) a place to leave the patient either for a temporary period (a respite for the family) or in a permanent way. The main issues discussed were the delays in the patients' referral to the hospice and the lack of time for long-term interventions; explicit focus is placed on the care by addressing the spiritual and emotional needs of caregivers, unlike in hospital settings where professionals avoid discussions of spiritual needs due to a lack of time, inadequate training and poor understanding of spirituality; hospices' interventions are based upon an ethos similar to the movement's original Christian spirit with emphasis placed on qualities of care such as love, charity, and compassion besides expertise and end-of-life competence, all while tolerating a sense of abandonment by health and social security systems following the patient's referral.